2012
DOI: 10.3390/cryst2020362
|View full text |Cite
|
Sign up to set email alerts
|

Polyoxotungstate-Surfactant Layered Crystal toward Conductive Inorganic-Organic Hybrid

Abstract: A polyoxotungstate-surfactant hybrid layered compound was synthesized as a single phase by using decatungstate ([W 10 O 32 ] 4− , W 10 ) and hexadecylpyridinium (C 16 py).The X-ray structure analysis combined with infrared spectroscopy and elemental analysis revealed the formula to be (C 16 py) 4 [W 10 O 32 ] (C 16 py-W 10 ). The layered structure consisted of alternative stacking of W 10 inorganic monolayers and interdigitated C 16 py bilayers with layered periodicity of 23.3 Å. Each W 10 anion in the W 10 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
33
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 14 publications
(36 citation statements)
references
References 52 publications
2
33
1
Order By: Relevance
“…Crystallographic data of Crystal 1 were collected using R-AXIS RAPID Scheme 1. The structure of (3-F-4-MeAnis + ), (3-IAnis + ), [18] …”
Section: Materials and Measurementsmentioning
confidence: 99%
See 3 more Smart Citations
“…Crystallographic data of Crystal 1 were collected using R-AXIS RAPID Scheme 1. The structure of (3-F-4-MeAnis + ), (3-IAnis + ), [18] …”
Section: Materials and Measurementsmentioning
confidence: 99%
“…Single crystal X-ray diffraction analysis revealed that the supramolecular Crystal 1 crystallizes in the triclinic space group Pī ( Table 1). The asymmetric unit is composed of one [SMo 12 O 40 ] polyoxoanion, two (3-F-4-MeAnis) cations, two [18]crown-6 molecules, and one CH 3 CN molecule and contains as many as 179 atoms. In the crystal structure, two types of supramolecular cations with anti-paralleled arrangement can be observed as shown in Figure 1, viewed along the c-axis.…”
Section: Materials and Measurementsmentioning
confidence: 99%
See 2 more Smart Citations
“…They have already been known for two centuries [1,2], and found numerous applications in a multitude of areas ranging from catalysis to pharmacology and remain of continuous interest, especially in the areas of design and synthesis of functional nanomaterials [3,4]. Polyoxotungstates occupy a special position among POMs, due to a multitude of fascinating structures and a wide scope of current and potential applications [5][6][7][8][9].…”
Section: Introductionmentioning
confidence: 99%